Spinal Accessory Nerve Duplication: A Case Report and Literature Review - Eleni Papagianni; Panagiota Kosmidou; Sotiria Fergadaki; Athanasios Pallantzas; Panagiotis Skandalakis; Dimitrios Filippou (Case Reports in Otolaryngology)
Aim of the present study is to expand our knowledge of the anatomy of the 11th cranial nerve and discuss the clinical importance and literature pertaining to accessory nerve duplication. We present one case of duplicated spinal accessory nerve in a patient undergoing neck dissection for oral cavity cancer. The literature review confirms the extremely rare diagnosis of a duplicated accessory nerve. Its clinical implication is of great importance. From this finding, a further extension to our knowledge of the existing anatomy is proposed.